PERHITUNGAN KAPASITAS PRODUKSI BERDASARKAN TINGKAT KEBUTUHAN BAHAN BAKU - Dewi Puspasari; Sukemi; Yus Djunaedi Rusli (ULTIMA Management, 2026)
Introduction/Main Objectives: UMKM Sate Abah Uteng , a typical Maranggi satay business from Plered , Purwakarta which was founded in 1990, experienced problems in maintaining the quality of raw materials, consistent and efficient production, as well as calculating the need for raw materials against consumer demand . Background Problems: This research focuses on calculating production capacity based on the level of raw material requirements . Novelty: focuses on calculating production capacity based on the level of raw material requirements . Research Methods: are used to analyze raw material needs and production capacity . Findings/Results: The analysis results show that the Economic Order Quantity EOQ for all raw materials is 0, so no orders need to be placed. Production capacity is not limited by the availability of raw materials, but by the number of workers available. Daily production should be in the range of 200 to 500 skewers with a number of workers of 1 to 3 people.